Beijing process and follow-up : Bangladesh perspective - Huq, Jahanara; Sālāhauddina, Khāledā; Hāmidā Ākhatāra Begama, 1941- (Women for Women, 1997)
On gender equality and justics; papers relating to the Workshop on Beijing Process and its Follow-up in Bangladesh.